1992
DOI: 10.1037/0021-9010.77.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Three approaches to the investigation of subgroup bias in performance measurement: Review, results, and conclusions.

Abstract: Three methods of assessing subgroup bias in performance measurement commonly found in the literature are identified. After a review of these approaches, findings are reported from analyses of data collected in the United States Army's Project A (J. P. Campbell, 1987). Correlations between nonrating performance measures and supervisor ratings were generally not moderated by race, but correlations between nonrating indicators of negative performance and ratings assigned by peers were. In addition, significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 31 publications
1
42
1
Order By: Relevance
“…White raters evaluated the average white ratee higher than 64 percent of black ratees; black raters evaluated the average black ratee higher than 67 percent of white ratees. Other researchers (Oppler, Campbell, Pulakos, & Borman, 1992;Sackett & Du Bois, 1991) have had similar findings. In a recent article, Stauffer and Buckley (2005) challenged personnel psychologists' belief that supervisory ratings of job performance are not biased by race.…”
Section: Research On Trainingsupporting
confidence: 72%
“…White raters evaluated the average white ratee higher than 64 percent of black ratees; black raters evaluated the average black ratee higher than 67 percent of white ratees. Other researchers (Oppler, Campbell, Pulakos, & Borman, 1992;Sackett & Du Bois, 1991) have had similar findings. In a recent article, Stauffer and Buckley (2005) challenged personnel psychologists' belief that supervisory ratings of job performance are not biased by race.…”
Section: Research On Trainingsupporting
confidence: 72%
“…As there is a greater percentage of minorities in the military than in the civilian workforce, military raters may be more accustomed to rating minority performers. Oppler, Campbell, Pulakos, and Borman (1992), again using the Army data, found that supervisor ratings were more performance-related and less influenced by ratee race than were peer ratings. Additionally, they found much higher agreement between black and white supervisors than between black and white peers, regardless of the race of the ratee.…”
Section: Gender-specific Performance Expectationsmentioning
confidence: 99%
“…The simplest example of this method is school assessment of five numerically expressed levels. They can be continuous and discontinuous, that is, they may have many levels, and it is possible to use different characters, lines, verbal designations, that is, adjectives (bad, above-average, average, below-average, excellent) ( Figure 2) [7,8].…”
Section: Graphic Scalesmentioning
confidence: 99%